The usefulness of accounting information quality in estimating future growth of companies - Hossein Etemadi, Aidin Kiani, Mohammad Ali Aghaei, (Opción, 2019)
The purpose of this study was to determine the priority and measure the usefulness of qualitative factors of financial reporting affecting future growth of companies. This research is applied in terms of purpose and quasi-experimental in terms of the test method. As a result, applying interactive effects of financial reporting quality variables and life cycle stages and economic conditions will increase the accuracy of the estimation of future growth of companies. In conclusion, with the predictive ability, using the interactive effects the financial reporting quality, life cycle and economic situation criteria increase.